1996
DOI: 10.1152/ajplung.1996.271.4.l637
|View full text |Cite
|
Sign up to set email alerts
|

Ion transport mechanisms in native rabbit nasal airway epithelium

Abstract: Net ion transports in rabbit nasal airway epithelium (RNAE) were estimated from unidirectional fluxes of 22Na+, 36Cl-, and 86Rb+ (K+ tracer), short-circuit current (Isc), and epithelial conductance (Gt) under short-circuit conditions in excised parallel RNAE from the two sides of the nasal septum mounted in Ussing chambers at 37 degrees C. Net Na+ absorption (JNa; 76 nmol.min-1.cm-2) was nearly equal to the net charge flux (Jnet), equivalent to the control Isc of 137 microA/cm2 (Jnet = Isc/zF = 85 neq.min-1.cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
36
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 0 publications
6
36
2
1
Order By: Relevance
“…Such data are in contrast to our previous observations from natural rabbit nasal airway epithelium where amiloride was demonstrated to induce a large (26%) decrease in G t simultaneous with a similar (25%) decrease in passive m-to-s Cl − fluxes [33]. Furthermore, our recent study on cellular effects of nucleotides strongly suggested that stimulation of apical purinergic P2Y 2 receptors caused a rapid inhibition of the conductance of the paracellular pathway [30].…”
Section: Introductioncontrasting
confidence: 97%
See 4 more Smart Citations
“…Such data are in contrast to our previous observations from natural rabbit nasal airway epithelium where amiloride was demonstrated to induce a large (26%) decrease in G t simultaneous with a similar (25%) decrease in passive m-to-s Cl − fluxes [33]. Furthermore, our recent study on cellular effects of nucleotides strongly suggested that stimulation of apical purinergic P2Y 2 receptors caused a rapid inhibition of the conductance of the paracellular pathway [30].…”
Section: Introductioncontrasting
confidence: 97%
“…Under short-circuit conditions, unidirectional fluxes of Cl − in native rabbit nasal airway epithelium are large and approximately fourfold greater than passive Na + fluxes, while net Cl − transport is close to zero or slightly secretory [33,34]. Furthermore, unidirectional Cl − fluxes vary proportionally with the epithelial conductance (G t ) (while this does not apply to passive Na + or non-electrolyte fluxes [5,33]).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations